Xiaoyaosan exerts anxiolytic-like effects by down-regulating the TNF-α/JAK2-STAT3 pathway in the rat hippocampus - Xiao-Juan Li (Nature Portfolio, 2017)
Abstract Although the anxiolytic-like effects of Xiaoyaosan, a Chinese herbal formula, have been described in many previous studies, its underlying mechanism remains undefined. The cytokine tumour necrosis factor-α (TNF-α) and its closely associated janus kinase 2 (JAK2)-signal transducer and activator of transcription (STAT3) signalling pathway regulate the neuro-inflammatory response in the brain, thus participating in the development of anxiety. Our purpose was to investigate whether the anxiolytic-like effects of Xiaoyaosan are related to the TNF-α/JAK2-STAT3 pathway in the hippocampus. We examined the effects of Xiaoyaosan on behaviours exhibited in the elevated plus maze test, open field test and novelty-suppressed feeding test as well as hippocampal neuron damage and changes in the TNF-α/JAK2-STAT3 pathway in a rat model of chronic immobilization stress (CIS)-induced anxiety. Xiaoyaosan exerts anxiolytic-like effects on CIS-induced anxiety, with a significant alleviation of anxiety-like behaviours, an attenuation of hippocampal neuron damage, and a reversal of the activation of the TNF-α/JAK2-STAT3 pathway in the hippocampus that are similar to the effects of the JAK2 antagonist AG490. However, Xiaoyaosan and AG490 failed to effectively regulate apoptosis-related factors, including Bax and Caspase-3. These results suggest that Xiaoyaosan attenuates stress-induced anxiety behaviours by down-regulating the TNF-α/JAK2-STAT3 pathway in the rat hippocampus.